Temática racial: práticas docentes nos anos iniciais do Ensino Fundamental - Silva, Anna Julia Gioielli Cardoso e [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The present work presents data for a survey qualitative basis of empirical on teaching practices focused on racial themes. The data presented were collected by means of the answers to a questionnaire applied to six teachers that act in the initial years of Elementary School in two municipal schools in the city of Ibitinga. The analysis of the practices manifested in the teachers answers aims to understand the teaching action in situations that involve the racial themes in the classroom, seeking to identify if the pipelines contribute to the (de) construction of prejudice and for a performance more aware of the issues that permeate everyday school life. The research revealed that the teachers have a certain awareness about the theme, however, there is still a lack of in-depth knowledge about the, which also leads to practices and positions considered racist what naturalizes situations of discrimination, which can influence negatively in the construction of students identity. It was also observed that there are no actions teachers training intentionally focused on the racial theme.
Keywords: Prática de ensino; Professores de ensino de primeiro grau; Ensino fundamental; Education